Genetically Determined ABO Blood Group and its Associations With Health and Disease. Issue 3 (March 2020) - Groot, Hilde E.; Villegas Sierra, Laura E.; Said, M. Abdullah; Lipsic, Erik; Karper, Jacco C.; van der Harst, Pim
Abstract : Objective: To determine the spectrum of phenotypes linked to the ABO blood group system, using genetic determinants of the ABO blood group system. Approach and Results: We assessed the risk of 41 health and disease outcomes, and 36 linear traits associated with the ABO blood group system in the UK Biobank cohort. A total of 406 755 unrelated individuals were included in this study. Blood groups A, B, and O were determined based on allele combinations of previously established single-nucleotide polymorphisms rs8176746, rs8176719 in the ABO gene. Group AB was excluded because of its relative small sample size. Overall, 187 387 (46%) were male with a mean (SD) age of 57±8.1 years and a median total exposure of 64 person-years (interquartile range, 57–70). Of 406 755 individuals, 182 621 (44.9%) participants had blood group O, 182 786 (44.9%) had blood group A, and 41 348 (10.2%) had blood group B. ABO blood groups were associated with 11 health and disease outcomes ( P <2.19×10 −4 ). ABO blood groups were primarily associated with cardiovascular outcomes. Compared with individuals with blood group O, blood groups A and B were associated with increased odds of up to 1.56 (95% CI, 1.43–1.69) for thromboembolic events and decreased odds for hypertension (0.94 [95% CI, 0.92–0.97]). Conclusions: The ABO blood group system is associated with several parameters of healthy aging and disease development. Knowledge of ABO blood groups might be of interest for more personalized approaches towards health maintenance and the prevention of diseases. Abstract : Supplemental Digital Content is available in the text.